Using Classroom Episodes to Foster Prospective Teachers’ Didactical Knowledge: Issues for Teacher Education - Tomás Ferreira, Rosa (2012)
After briefly analysing a classroom episode, we discuss aspects of the teacher’s didactical knowledge, namely in its mathematical and instructional dimensions, as reflected in the answers of three prospective teachers to a written assignment based on the episode. We then raise some issues regarding initial teacher education, anchored in the notion of didactical knowledge.